Efficacy of Sublingual Immunotherapy with Dermatophagoides farinae Extract in Monosensitized and Polysensitized Patients with Allergic Rhinitis: Clinical Observation and Analysis. (27th April 2015) - Xu, Chen-Xia; Zhang, Miao-Lian; Li, Bi-Zhou; He, Ying; Zou, Ze-Hong; Wu, Qiu-Rong; Tao, Ai-Lin; Lai, He; Sun, Jin-Lu
Abstract : Aim . To investigate differences in the efficacy of sublingual immunotherapy with Dermatophagoides farinae drops in monosensitized and polysensitized allergic rhinitis patients. Methods . The patients enrolled in the study were treated for more than one year by sublingual immunotherapy (SLIT) using Dermatophagoides farinae drops and were divided into a monosensitized group (n = 20 ) and a polysensitized group (n = 30 ). Total nasal symptom scores of patients before and after SLIT were analyzed to evaluate the curative effect. The phylogenetic tree of dust mite allergens as well as other allergens that were tested by skin prick test was constructed to help the analysis. Results . There was no significant difference in the efficacy of SLIT between dust mite monosensitized and polysensitized patients. Conclusions . Both dust mite monosensitized and polysensitized patients could be cured by SLIT using Dermatophagoides farinae drops. This study provides a reference for the selection of allergens to be used in immunotherapy for polysensitized AR patients.